EFEKTIFITAS KINERJA PEGAWAI NEGERI SIPIL (PNS) DI KANTOR BADAN KEPEGAWAIAN DAERAH (BKD) KABUPATEN MINAHASA SELATAN - Tiwow, Alfa (JURNAL EKSEKUTIF, 2014)
Performance of an employee within a company or agencies is a measure of the success or failure of goals and job responsibilities as set out in the such of company or agencies. Each employee has a responsibility in carrying out their respective duties and works. Effectiveness of employee performance is closely related to the workings of the employees themselves in carrying out the responsibilities given to him. Civil servants in the office staffing agency South Minahasa district there are not responsible in performing their duties so that the purpose of the agency is not achieved. The purpose of this study to determine the performance of the employees in terms of capabilities, business and employment opportunities as well as the effectiveness of the approach is a source of employees, processes and objectives. This research used qualitative methods in the form of a descriptive case study approach. The results showed that the organizations objectives and strategies of the office staffing agency in South Minahasa district based on the duties that had been arranged by the employer or the Regent of South Minahasa, while performance measurement indicators based programs or activities that have been arranged or composed. The level of achievement of the goals and objectives of the organization still follows the coordination of each program according to the achived of results. In terms of employee performance evaluation, judging from the description of duties and responsibilities that exist whether in accordance with predetermined. Overall performance of the office staffing agency in South Minahasa district has not been too good because there are still many shortcomings in the office itself or its employees. Keywords: effectiveness, performance, civil servants